2018
DOI: 10.1002/jcp.27281
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D: A new mediator during high phosphate‐induced vascular calcification associated with chronic kidney disease

Abstract: Vascular calcification (VC) is the pathological accumulation of calcium phosphate crystals in one of the layers of blood vessels, leading to loss of elasticity and causing severe calcification in vessels. Medial calcification is mostly seen in patients with chronic kidney disease (CKD) and diabetes. Identification of key enzymes and their actions during calcification will contribute to understand the onset of pathological calcification. Phospholipase D (PLD1, PLD2) is active at the earlier steps of mineralizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Currently, aortic rings from rats and mice are commonly used for studying vessel calcification under various conditions. The stimulation time varies from 3-14 days [6,24,25,28,59,[62][63][64][65]. Although the utilization of aortic rings comes closer to the physiologic setting, a multitude of influencing factors is still lost.…”
Section: Ex Vivo Modelsmentioning
confidence: 99%
“…Currently, aortic rings from rats and mice are commonly used for studying vessel calcification under various conditions. The stimulation time varies from 3-14 days [6,24,25,28,59,[62][63][64][65]. Although the utilization of aortic rings comes closer to the physiologic setting, a multitude of influencing factors is still lost.…”
Section: Ex Vivo Modelsmentioning
confidence: 99%
“…While the former is regarded as a potent inhibitor, the latter serves as an inducer for calcium deposition. 47,48 For the treatment, as discussed above, the cells were viable when treated with the PSI-OA NPs up to the tested concentration of 640 μg/mL (3 days of incubation). However, as indicated above, Cur at high concentration (32 μg/mL) was toxic to the cells after 3 days of incubation.…”
Section: Acsmentioning
confidence: 99%
“…VSMCs are the main mediator for vascular calcification because they trans-differentiate into osteogenic cells under pathological conditions, facilitating calcium deposition. [32][33][34] A variety of studies have shown that the chelation ability of PASP results in the prevention of calcium precipitation and deposition. 2 Considering these results, we expect that because PASP is spontaneously synthesized by the gradual hydrolysis of PSI NPs, calcification of VSMCs would be prevented.…”
Section: Prevention Of Calcification Of Vascular Smooth Muscle Cells ...mentioning
confidence: 99%
“…7B). 32,33 ALP is a well-known enzyme that catalyzes the hydrolysis of pyrophosphates to inorganic phosphate. While the former is regarded as a potent inhibitor, the latter serves as an inducer for calcium deposition.…”
Section: Prevention Of Calcification Of Vascular Smooth Muscle Cells ...mentioning
confidence: 99%